2015
DOI: 10.1177/0016986215597748
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Well-Being of Gifted American College Students

Abstract: This study examined the psychometric properties of the Personal Well-being Index for Adults (PWI-A), a measure of subjective well-being. The study used data from 533 high-ability American college students: honors students and participants in an early college entrance program. In earlier studies using the PWI-A, the instrument appeared to show differences in disaggregated aspects of well-being for these gifted college students. Unfortunately, the careful psychometric examination of the instrument done in this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…On the other hand, the two-factor model (factor one: standard of living, health, achievement, and safety; factor two: relationships, community connectivity, future security) yield a poor model fit (RMSE > 0.08, CFI <0.95). 27 In this study, the OCFA validated the results suggested by the OEFA. The two-factor model had a more adequate fit rather than the single-model (AIC = 52.64 and 62.77, respectively, RMSE = 0.084 (90% CI = 0.01-0.14), and 0.119 (90% CI = 0.07-0.17), respectively, and CFI = 0.964, and 0.922, respectively).…”
Section: Discussionsupporting
confidence: 78%
“…On the other hand, the two-factor model (factor one: standard of living, health, achievement, and safety; factor two: relationships, community connectivity, future security) yield a poor model fit (RMSE > 0.08, CFI <0.95). 27 In this study, the OCFA validated the results suggested by the OEFA. The two-factor model had a more adequate fit rather than the single-model (AIC = 52.64 and 62.77, respectively, RMSE = 0.084 (90% CI = 0.01-0.14), and 0.119 (90% CI = 0.07-0.17), respectively, and CFI = 0.964, and 0.922, respectively).…”
Section: Discussionsupporting
confidence: 78%
“…Gifted students in honors and TAMS programs at the University of North Texas showed similar levels of personal well-being at admission to the programs as freshmen. Both groups scored above the expected homeostatic range of adolescents in general (Sayler, Boazman, Natesan, & Periathiruvadi, 2015). They differed in being more satisfied with their standard of living, achievement, and personal safety and they were less satisfied with personal relationships and their sense of community.…”
Section: Studies On the Psychosocial And Familial Characteristics Of mentioning
confidence: 78%
“…The present study considers giftedness as an essential personal factor that has an impact on well-being and psychosocial adjustment. All these issues are of importance for gifted children and adolescents and their families [5], as well as for the professionals working with them: teachers, psychologists, doctors, etc. [25].…”
Section: Discussionmentioning
confidence: 99%
“…SWB is particularly important in childhood and adolescence, as the foundation for mental health is being laid, and school is an important means to promote SWB [4]. These are all issues of importance for gifted children and adolescents and their families [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation